Assuring the Quality of Teaching at Makerere University in Uganda: Practices and Experiences of Academics and Students - Nabaho, Lazarus; Aguti, Jessica N.; Oonyu, Joseph (Alternation Journal, 2016)
Quality is an ethos in academia and assuring it is top of the agenda at many universities. Since the 1990s, substantial research has been conducted on the quality assurance systems of developed countries with advanced higher education systems. However, literature on quality assurance systems in the context of Sub-Saharan Africa is limited. The study examined the practices and experiences of stakeholders at the student-academic interface in assuring the quality of teaching at Makerere University. A case study design was employed and respondents included academics and final-year students. Data was collected through documents review, interviews and focus group discussions. Thematic analysis and content analysis were used to analyse the data. The findings demonstrate that the university employs five practices to assure the quality of teaching, namely, recognition of teaching, student evaluation of teaching, pedagogical training, monitoring and supervision of teaching, competence-based deployment and interfacing. The findings further show that stakeholders had varying experiences of teaching quality assurance practices.
Keywords: Quality; Quality assurance; Good teaching; Practices